Platform employment as the main trend in the development of the labor market in modern conditions in Kazakhstan - Kuttybayeva, N.B.; Zhakina, G.E.; Makalakova, B.M.; Rakhimova, A.N.; Uskenbayeva, D.A. (BUKETOV BUSINESS REVIEW, 2024)
Object: Consider various definitions of platform employment, systematize theoretical approaches to analyzing new forms of employment organized with the use of digital technologies, assess the prevalence of platform employment in Kazakhstan, and systematize the positive and negative aspects of the development of platform employment in the country. Methods: In the study methods of statistical and econometric analysis, as well as comparison were used. Findings: Based on various definitions of platform employment, a theoretical approach to the analysis of new forms of employment organized using digital technologies was systematized and an assessment of the scale of platform employment was carried out. The assessment of the scale of platform employment in Kazakhstan revealed the strengths and weaknesses of platform employment in the country. Conclusions: Theoretical approaches to the analysis of new forms of employment organized using digital technologies were systematized. Based on the definitions, the scale of platform employment in Kazakhstan was assessed. This indicator tends to increase in the long term, but with slight fluctuations in numbers from year to year in the short term. Based on the systematization of definitions of platform employment and assessment of the scale of platform employment in Kazakhstan, the strengths and weaknesses of platform employment were identified.